EVALUASI KINERJA HUTAN KEMASYARAKATAN GAPOKTAN ALAM LESTARI RESORT JANGKOK KESATUAN PENGELOLAAN HUTAN RINJANI BARAT - Ananda, Siti Munawarah; Setiawan, Budhy; Valentino, Niechi (AGROTEKSOS, Jurnal Ilmiah Ilmu Pertanian, 2023)
NTB Province is committed to implementing the Ministry of Environment and Forestry Regulation Number 9 of 2021 which states that there is a need to increase the economic activities of residents living around forests through social forestry schemes. The most popular social forestry scheme is HKm. The HKm scheme is of more interest to the people of NTB because it aims to improve the welfare of communities around the forest and its implementation can be carried out in protected and production forests. Based on the above problems, it is necessary to conduct research related to the evaluation of HKm management of Gapoktan Alam Lestari in order to find out the economic, ecological and social aspects regulatedinPerdirjen Perhutanan Sosial dan Kemitraan Lingkungan No.P.9/PSKL/PKPS/KUM.1/10/2019. Descriptive method was used in this research. A snowball sampling approach was used to determine respondents. Gapoktan Alam Lestari obtained a medium score (75%) in its evaluation.